Biosafety Management Practices Among Clinical Laboratory Professionals in Debre Berhan Town Governmental Hospitals, Ethiopia: A Cross‐Sectional Study - Mahlet Tewodros Tadesse; Libse Lemma Ayalke; Beza Fitiwi Tedla; Fikrite Adefris Weldemeskel; Ahmed Seid Yirdaw; Tsegahun Asfaw Abebe (Health Science Reports)
Abstract Background and Aims Clinical laboratories play a vital role in modern healthcare, where laboratory test results significantly influence medical decisions. However, laboratory professionals are often exposed to hazardous biological materials, underscoring the importance of biosafety management. This study aimed to assess biosafety practices among clinical laboratory professionals in Debre Berhan town, Ethiopia. Methods A cross‐sectional study involving 81 participants was conducted using a standard questionnaire covering work habits, protective barriers, safety equipment, and biosafety policy perception. Descriptive data was summarized using a table and graph. Logistic regression was employed to determine factors affecting adherence to biosafety protocols. Statistically significant value was identified using p value ≤ 0.05, 95% CI, and OR. Results The results revealed high compliance with essential work habits, such as the use of mechanical pipettes 77 (95.1%) and proper handwashing after handling biohazardous material 78 (96.3%) and after removing gloves 80 (98.8%). However, adherence to the use of protective barriers 50 (61.7%), biosafety training 15 (18.5%), and emergency preparedness 28 (34.6%) were notably low. Only 35 (43.2%) of participants received appropriate immunizations, and access to biosafety equipment like biological safety cabinets was limited 15 (18.5%). Experience and training were significant predictors of biosafety compliance, highlighting the need for continuous education and institutional support. Conclusion The findings underscore the importance of enhancing training programs, improving access to safety equipment, and ensuring the consistent application of biosafety protocols to protect laboratory personnel from hazardous biological materials and maintain public health.